Corrosion rate of anodized AA 7075-T651 on H2SO4 electrolyte and vVoltage variation - Moch. Syamsul Ma'arif; Muhammad Noviandari; Rudy Soenoko (University of Muhammadiyah Malang, 2023)
Metal materials corrode because of an electrochemical process that damages or destroys them gradually. In addition to chemical reactions, high temperatures, mechanical operations, and rainfall exposure can all lead to corrosion. It is an experimental study with variation of voltage for AA 7075-T651. The voltage variation between 4 and 5 and 6 volts is the independent variable employed in this study. The rate of corrosion and the size of the pores are the dependent variables. One amp of current, thirty millimeters between the anode and cathode, one millimeter of sulfuric acid as the electrolyte concentration, and ten minutes of anodizing time are the controlled variables in this study. Variation in voltage throughout the anodizing process can regulate how quickly corrosion occurs via the oxide layer that is created. The 7075-T651 series aluminum alloy, when subjected to action anodizing at different voltages of 4 volts, 5 volts, and 6 volts, yields pore diameters measuring 0.273 μm, 0.436 μm, and 0.522 μm, respectively, according to SEM picture data.